Dynamic De/Centralization in Federations: Comparative Conclusions. Issue 1 (28th November 2018) - Dardanelli, Paolo; Kincaid, John; Fenna, Alan; Kaiser, André; Lecours, André; Singh, Ajay Kumar; Mueller, Sean; Vogel, Stephan
Abstract: This article presents the conclusions of the project Why Centralization and Decentralization in Federations?, which analyzed dynamic de/centralization in Australia, Canada, Germany, India, Switzerland, and the United States over their entire life span. It highlights six main conclusions. First, dynamic de/centralization is complex and multidimensional; it cannot be captured by fiscal data alone. Second, while centralization was the dominant trend, Canada is an exception. Third, contrary to some expectations, centralization occurred mainly in the legislative, rather than fiscal, sphere. Fourth, centralization is not only a mid-twentieth century phenomenon; considerable change occurred both before and after. Fifth, variation in centralization across federations appears to be driven by conjunctural causation rather than the net effect of any individual factor. Sixth, institutional properties influence the instruments of dynamic de/centralization but do not significantly affect its direction or magnitude. These findings have important conceptual, theoretical, methodological, and empirical implications for the study of federalism.